Can Training Background Offset the Disadvantage Associated With Relative Age Effect on Perceptual-Cognitive Skills From Childhood Into Adolescence? - Zhang, Xiaoyu; Maso, Freddy; Ekpe-Lordonnois, Brigitte; Poncelet, Tom; Ennequin, Gael; Blazevich, Anthony J.; Ratel, Sébastien (Pediatric Exercise Science, 2026)
Purpose : The aim of this study was to investigate the extent to which relative age effect (RAE) impacts the development of perceptual-cognitive skills and how training background may potentially offset RAE from childhood into adolescence. Method : One hundred sixty-five 10- to 16-year-old male participants were divided into 8 groups based on their birth quartiles (BQ 1 [January–March], BQ 2 [April–June], BQ 3 [July–September], and BQ 4 [October–December]) and training background (moderately trained: 1–2 sessions/wk and well-trained: 4–5 sessions/wk). Their perceptual-cognitive skills were evaluated using a 3D multiple-object tracking task (ie, the NeuroTracker [NT]) with (3D) and without (2D) stereopsis. Results : In moderately trained children, NT scores progressively decreased from BQ 1 to BQ 4 , with a significant difference between the first 3 birth quartiles and BQ 4 (P <.01), independent of stereopsis. In well-trained children, however, no significant differences were detected in NT scores between quartiles, and well-trained children in BQ 4 exhibited NT scores comparable to moderately trained children in the first 3 quartiles. Conclusion : RAE showed a significant disadvantage on the perceptual-cognitive scores in moderately trained children born in BQ 4. However, well-trained children born in BQ 4 performed similarly to other well-trained children and to moderately trained children born in the first 3 birth quartiles, meaning that training background may offset the disadvantage associated with RAE from childhood into adolescence.